Removal of herbicides in a biopurification system is not negatively affected by oxytetracycline or fungally pretreated oxytetracycline - Cambronero Heinrichs, Juan Carlos (2018)
UCR::Vicerrectoría de Investigación::Unidades de Investigación::Ciencias Básicas::Centro en Investigación en Contaminación Ambiental (CICA)